Les premiers partis politiques cubains et leur influence dans la constitution de l’Etat-nation (1878-1902) - Dominique Soucy (Les Cahiers ALHIM)
The truce decreed by the Agreement of Zanjón, which put an end to the first war of Cuban independence (1868-1878), established a new context that would allow the organization of a political local life that became institutionalized from the creation of the first political parties in 1878, especially the Partido Liberal Autonomista and the Unión Constitucional. Around of these two groups – first one progressive, the second conservative - the insular elites were going to be able to exercise in the political game and to develop a Cuban political culture impregnated with particularities and contradictions that would be reflected more or less reflected in the Constitution of 1901 and the Republic proclaimed in 1902. The present article focus on the inheritance left by these two political parties - generally isolated from the process of national construction by the classic historiography - in the constitution of a Cuban political identity.